Rekonstruksi Model Pendidikan Islam Masa Rasulullah dalam Konteks Pendidikan Modern Abad 21 - Muhammad Saiful Hidayat; Khassan Masyath; Kreista Sreshi Indratno; Avinda Putri Awaliyah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to reconstruct the Islamic education model during the time of the Prophet Muhammad in the context of 21st-century modern education. This research employs a qualitative descriptive method using a literature review as its research type. Data was collected and analyzed from various relevant literature sources, such as the books of the Prophet's biography (sirah nabawiyah), Qur'anic commentaries (tafsir), books on Islamic education, and academic journals. The research findings indicate that the Islamic education model during the Prophet's time has high relevance to the challenges of modern education. Noble values such as faith, piety, good morals, and knowledge taught by the Prophet are essential in shaping quality young generations. However, in the context of modern education, the Islamic education model needs to be reconstructed by adapting teaching methods, developing relevant curricula, and utilizing technology. This study concludes that the reconstruction of the Islamic education model is a crucial endeavor to produce young generations who are faithful, knowledgeable, and virtuous, thus enabling them to face the challenges of the times.